Tindak Pidana Penipuan Dalam Jual Beli Online - Purba, Boni; Wirasila, A. A. Ngurah (Kertha Wicara : Journal Ilmu Hukum, 2020)
The purpose of this paper is to determine what legal substance will be used when processing criminal acts of online buying and selling fraud. The focus of analysis in this paper is Article 28 paragraph (1) of the ITE Law and Article 378 of the Criminal Code. It is feared that the articles will cause obscure norms to the elements in them. The research method used is Normative, namely research that uses a statutory approach in accordance with the problems in this journal. After analyzing Article 28 paragraph (1) of the ITE Law and Article 378 of the Criminal Code, the results obtained are that the two articles regulate different things but there are identical things that the two articles have. The two articles have one thing in common, namely causing harm to others. However, the formulation of Article 28 paragraph (1) of the ITE Law does not require an element of "benefiting oneself or others" as stipulated in Article 378 of the Criminal Code concerning fraud. Article 28 paragraph (1) of the ITE Law regulates consumer losses in online buying and selling transactions caused by fake news, while Article 378 of the Criminal Code regulates fraud. This can be overcome by applying the principle or legal doctrine of lex specialis derogate legi generalis. This is because article 28 paragraph (1) of the ITE Law has more specific element characteristics compared to Article 378 of the Criminal Code in the context of punishment for online fraud crimes, it can be said that article 28 paragraph (1) of the ITE Law is lex specialis derogat legi generalis from article 378 Criminal Code.     Key Words:  Buy and sell Fraud, Crime.